2017
DOI: 10.1136/injuryprev-2017-042371
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of traumatic brain injury with loss of consciousness

Abstract: One in five adults experienced TBIs of sufficient severity to cause LOC; 3% experienced at least one moderate or severe TBI and almost 10% experienced a first TBI with LOC before the age of 15 years. The prevalence of lifetime TBI in the present study suggests that there may be a substantially greater burden of injury than concluded from previous prevalence estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…T raumatic brain injury (TBI) of all severities is one of the greatest health care-related problems facing our country and the entire world today [1][2][3][4]. The majority of the 1.7 million estimated TBIs occurring in the United States each year are mild [5].…”
Section: Introductionmentioning
confidence: 99%
“…T raumatic brain injury (TBI) of all severities is one of the greatest health care-related problems facing our country and the entire world today [1][2][3][4]. The majority of the 1.7 million estimated TBIs occurring in the United States each year are mild [5].…”
Section: Introductionmentioning
confidence: 99%
“…These questions were adapted from The Ohio State University TBI Identification Method (OSU TBI-ID) 11 12. A description of the module and its inclusion in the Ohio BRFSS is described elsewhere 9. The study used de-identified, archival data and thus was considered exempt from human subjects review by the host Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Consequences of TBI may not all be immediate and continuous, instead emerging or re-emerging later in life 1. Thus, examining lifetime exposure as a risk factor for current health and behavioural functioning would provide a more complete characterisation of the public health burden due to TBI 9. The objective of the current study was to examine the association between lifetime exposure to TBI and current physical health status and health-related risk behaviours among non-institutionalised adults in Ohio.…”
Section: Introductionmentioning
confidence: 99%
“…Estados Unidos causa más de 50,000 muertes, 280000 hospitalizaciones y 2.2 millones de ingresos al servicio de urgencias anualmente 6…”
Section: Corrigan Y Colaboradores (2017) Reportan Que Enunclassified